Modification of Chlorella vulgaris carbon with Fe3O4 nanoparticles for tetracycline elimination from aqueous media - Mohaddeseh Zahmatkesh Anbarani; Bahman Ramavandi; Ziaeddin Bonyadi (Heliyon, 2023)
Tetracycline (TTC) is an antibiotic commonly prescribed to treat bacterial infections in animals and humans because of its low toxicity and antibacterial activity. This study focuses on the removal of TTC from an aqueous media using an activated carbon of Chlorella vulgaris modified with Fe3O4 magnetic composite (ACCV/Fe3O4 mc). The isothermal and kinetic models were studied to understand the adsorption mechanism. The Box-Behnken model was used for experimental design, and the main research parameters were ACCV/Fe3O4 mc mass (0.2–0.8 g/L), reaction time (10–60 min), TTC concentration (5–30 mg/L), and pH (3–11). The highest TTC removal rate of 90.47% was obtained at a pH of 7, a time of 60 min, an ACCV/Fe3O4 mc mass of 0.5 g/L, and an antibiotic concentration of 5 mg/L. TTC removal was fitted with the pseudo-second-order and the Langmuir model. The Langmuir adsorption capacity of TTC was computed to be 26.18 mg/g. The results show that the ACCV/Fe3O4 mc adsorbent significantly removes TTC from the aqueous solution.